Oridonin attenuates TLR4-driven inflammation and autophagy in LPS-stimulated enteric glial cells: an in vitro and in silico analysis - Nemutlu Samur, Dilara; Boyacı, Aybüke; Maytalman, Erkan (Frontiers in Cellular Neuroscience, 2026)
IntroductionEnteric glial cells (EGCs) are key regulators of gut-brain axis immunity, and their excessive activation contributes to intestinal inflammation and neuroimmune disturbances implicated in early Parkinson’s disease. Oridonin, a diterpenoid compound with known anti-inflammatory and autophagy-modulating properties, has not been extensively studied in peripheral glial models. Here, we investigated the effects of oridonin on TLR4-mediated inflammatory signaling and autophagy responses in LPS-stimulated EGCs, with molecular docking used as a supportive, hypothesis-generating approach.MethodsRat-derived EGCs were exposed to LPS (10 μg/mL) to induce glial activation. Cells were treated with oridonin (1–5 μM) with or without the selective TLR4 inhibitor TAK-242. mRNA levels of TLR4, S100B, LC3, and beclin-1 were quantified by RT-qPCR, while caspase-1 and IL-1β protein levels were assessed by ELISA. Molecular docking was performed to explore potential interactions of oridonin and TAK-242 with the TLR4 receptor complex.ResultsLPS significantly increased TLR4 and S100B expression and upregulated the autophagy markers beclin-1 and LC3. Oridonin dose-dependently suppressed LPS-induced upregulation of TLR4 and S100B and attenuated the elevation of autophagy-related transcripts. Docking studies suggested that oridonin and TAK-242 may interact with regulatory regions of the TLR4 complex, including surface-exposed sites on the TLR4-MD-2 ectodomain and distinct sub-pockets within the intracellular TIR domain, with oridonin exhibiting a stronger predicted binding affinity. Although LPS increased TLR4 mRNA, it elicited only a modest increase in caspase-1 levels and no significant change in IL-1β levels, consistent with incomplete inflammasome activation. Whereas TAK-242 alone did not fully suppress IL-1β, combined treatment with oridonin reduced cytokine levels more effectively, suggesting complementary downstream modulation rather than direct receptor-level synergy.DiscussionOridonin exerts powerful anti-inflammatory and autophagy-modulating effects in EGCs by inhibiting TLR4-driven signaling, normalizing excessive autophagic responses, and limiting IL-1β output. Its dual capacity to suppress both upstream (TLR4/S100B) and downstream (caspase-1/IL-1β) components of the inflammatory cascade preserves EGC homeostasis under endotoxin stress. These findings highlight oridonin as a potential modulator of peripheral glial inflammation and support further investigation of its therapeutic potential in gut-brain axis disorders.